Teacher Development During and Beyond COVID-19: Perspectives from Zimbabwe (Teacher Education through Flexible Learning in Africa (TETFLE), 2022)
The purpose of the study is to examine how Zimbabwe teacher educators can develop pre-service and in-service teachers to teach effectively during the COVID-19 pandemic  and beyond. This qualitative study, guided by the case study strategy, gathered the perspectives of experienced teachers and teacher educators in Harare schools, teachers colleges and universities. Data were generated through face to face interviews, zoom meetings, WhatsApp and Google talk methods. Data were analysed using constant content analysis technique. The findings are, pre-service teachers and in-service teachers, acquire pedagogical,  and technological skills in addition to what they have been taught. Another finding is that teacher educators, pre-service and in-service teachers need knowledge and skills for implementing blended teaching and learning, On Demand Examination system, formative and summative assessment. It is concluded that the model for teacher development will continue to be blended learning. It is also concluded that teachers will be developed through the ODeL mode during a COVID-19 pandemic and beyond. It is recommended that technology infrastructure in Zimbabwe be upgraded, to allow lecturers, teachers and students access the internet with ease, in addition to training them in ICT skills and knowledge.Key words
Keywords: Teacher development; teacher educator; blended learning; COVID-19 pandemic